A new fossil Phyllotine (Rodentia, Sigmodontinae) from late Pliocene in the Andes of northern Argentina - Ortiz, Pablo Edmundo (2012)
Pardinamys humahuaquensis, a new genus and species of Phyllotini (Rodentia, Cricetidae), is described on the basis of 111 cranial, mandibular, and dental remains belonging to at least 29 individuals. The fossils were recovered from a microvertebrate assemblage found in late Pliocene deposits (between 3 and 2.5 Ma ago) from the Uqu´ıa Formation, central Jujuy Province, northwestern Argentina. †Pardinamys is morphologically intermediate between the extant genera Eligmodontia and Calomys and can be differentiated from these taxa by the combination of several traits, including short masseteric crest, with upper and lower ramus similarly developed; coronoid process well developed; anteromedian flexus in M1 only present in very young individuals, without any trace of anteromedian style; M1 and M2 with developed second minor fold; large M2 and M3; and metaflexus, paracone, and metacone of M3 well developed. The morphologic characteristics of the new genus and the other sigmodontines found in the Uquian assemblage (at least three extinct genera) suggest an important radiation before the establishment of the modern communities in the central Andean region and indicate the need for a reevaluation of the divergence-age estimates for the group. The recovered taxa indicate the presence of open environments during depositional times, within arid or semiarid conditions, unlike previous reconstructions for this geologic unit. The finding reveals the need for improving the fossil record of sigmodontines in the central Andean region and its importance to understanding the radiation of this group in a more inclusive South American context.